PERAN KELOMPOK PEMBUDIDAYA IKAN (POKDAKAN) ACI BAHARI DALAM PEMBUDIDAYAAN IKAN BANDENG DI DESA PESISIR KECAMATAN GENDING, KABUPATEN PROBOLINGGO - Mely Cahya Puspita; Aryo Fajar Sunartomo (University of Jember, 2019)
Probolinggo Regency is one of the production centers for milkfish producers in East Java. Milkfish has a very good prospect to be developed in the agribusiness especially in fisheries subsector. One of milkfish cultivators group that is known to be active in Probolinggo Regency is Aci Bahari Fish Cultivators Group (Pokdakan). This research aimed to explain the role of Aci Bahari Fish Cultivators Group (Pokdakan) on the cultivation of milkfish in Pesisir Village of Gending District, Probolinggo Regency. The research area was determined by purposive method in Pesisir Village. The research used descriptive qualitative method. Determination of informant conducted by purposive sampling. The methods used in collecting data are interviews, observation, and documentation. Data analysis method used is Miles and Huberman model. The results of the research showed that (1) The role of Aci Bahari Pokdakan as a learning class included the formulation of learning needs, routine group meetings, learning motivation, learning processes and the activeness of the group. (2) The role of Aci Bahari Pokdakan as a vehicle for cooperation included the atmosphere of cooperation, the division of tasks, deliberation of problems, planning of providing production facilities and cooperation with other production parties. (3) The role of Aci Bahari Pokdakan as a production unit included decision making, preparation of the group needs, technology facilities, implementation of group agreements and increasing production sustainability.